Penetapan Kadar Vitamin C dalam Sari Buah Nanas (Ananas comosus L. MERR) dengan Metode Spektrofotometri UV - Maya Syafira; Anny Sartika Daulay; Ridwanto Ridwanto; Haris Munandar Nasution (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Pineapple or which has the Latin name Ananas Comosus L. MERR has two main ingredients, namely vitamin C and manganese. Vitamin C is very important for the growth and development of the immune system and can help the absorption of iron from food, meanwhile manganese is a natural mineral that has antioxidant properties or can ward off evil compounds in the body and help increase the body's immunity to avoid the Covid-19 disease outbreak.. Therefore, researchers are interested in researching pineapple juice, because what people consume every day is pineapple juice. The aim of this research was to determine the levels of vitamin C in pineapple juice (Ananas comosus L. MERR) and whether the vitamin C content in pineapple juice (Ananas comosus L. MERR) can meet daily nutritional adequacy rates. This research method uses quantitative methods. Where is the relationship between the independent variable and the dependent variable. The independent variable is pineapple filtrate and the dependent variable is vitamin C content. The parameters of this research are vitamin C levels using the UV Spectrophotometry method. The conclusion of this study shows that the results of the examination of pineapple juice levels are 54.6816 21.6678 mcg/g, and the vitamin C content in pineapple juice can meet the daily nutritional adequacy figure, namely 33 mg to 76 mg.